Efektivitas Pelaksanaan Promosi Pegawai Negeri Sipil Pada Badan Kepegawaian Daerah Provinsi Sumatera Barat - Santika, Nola; Lanin, Dasman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The purpose of this study was to determine the Effectiveness of Implementation about the Civil Servants' Promotion at the Regional Employment Agency of West Sumatera and the factors that influence the Effectiveness of Implementation about the Civil Servants' Promotion at the Regional Employment Agency of West Sumatera. The type of research used is qualitative with descriptive method. Informants were determined by using purposive sampling technique. Data collection techniques were carried out by interview, observation and documentation. The results of the study explain that the effectiveness of the implementation about the Civil Servants' Promotion at the Regional employment Agency of West Sumatera can be said that is ineffective, this is because of there are still employees who occupy positions that are not in accordance with their educational background, so that it causes the capacity of employees to fulfill jobs in accordance with their duties which the principal and functions have not fully handled the work in their respective fields, which of course will make the quality of employees at work being low. The factors that affect the effectiveness of implementation about the civil Servants' at the Regional Employment Agency of West Sumatera, namely: the quality of human resources, competence of administrators, facilities and infrastructure, and supervision.